Menemukan keunikan budaya Indonesia tanpa terjebak dalam tren semu dan FOMO - Hawa', Zaffa Shofiyyul (Maliki Interdisciplinary Journal, 2024)
This article explores the importance of discovering and appreciating the uniqueness of Indonesian culture without getting caught up in pseudo-trends triggered by FOMO (Fear of Missing Out). In this information-rich digital era, we are often tempted to follow trends that are currently popular on social media, without really understanding the culture that is the basis for these trends. This article invites readers to broaden the horizons of the archipelago in an authentic way and study Indonesian culture in depth.